Why, at all, do we need Religion? Religion and Morality in Post-Communist Europe - Zrinščak, Siniša (Array, 2009)
Continuing debates about the secularization process in Europe, and particularly about the impact of secularization on different aspects of individual and social life, got one another dimension after 1989. Up to then officially atheist part of Europe collapsed and religion generally got new, previously unimaginable possibilities of public acting. This process, usually marked as revitalization process, started to dominate both social life and scientific researches. However, the story has been far from being clear. At least three parallel processes have been noticed and discussed. First, the revitalization of religion is clearly confirmed, at least on two basic grounds. The first one is connected with the role of Churches in public life. The pre-Communist time was not resurrected but (particularly dominant) Churches resumed much of their power lost after 1945. They re-established their official ties with states (in the case of the Catholic Churches by international agreements with the Holy See), they re-entered public schools, returned much of their properties and got big media attention. The second aspect was visible from the data on individual connections with Churches and / or religion. Although the base line was very different among different countries, they all noticed the trend of rising religiosity in the late 80s and early 90s. Although noticeable the revitalization trend did not occur in the same pace in different countries but, moreover, the striking thing is that differences in the level of religiosity among countries have remained so big, bigger than in Western Europe. Those who claim belonging to religious denomination range in 1999 from 97.6% in Romania and 95.7% in Poland through 70.0% and 57.7% in Bulgaria and Hungary respectively to only 33.5% and 24.8% in the Czech Republic and Estonia respectively. In the light of these data any speech about the revitalization for a large group of countries (even if it is, up to certain level, true) has become almost meaningless. Third and apart from the limited revitalization in some countries, many researches pointed out contradictory aspects of the new social life of religion. According to the existing sociological literature these contradictory aspects can be further subdivided in different branches. The majority of approaches paid attention to adaptation problem: Churches generally want to awake their pre-communist position what is hardly possible in changed modern world. Confused expectations from the public complicates the picture: at the same time the majority rejects political involvement and even public social role of Churches (epitomized in the phrase: priests should restrict their activities to Church buildings) but expect their involvement in public issues, such as rising poverty and inequality, rights of workers, etc. These contradictory expectations can be connected with very visible ideological (left-right) social division and debates about the proper role of Churches in modern world. The position of religious minorities in post-Communist Europe emphasizes the old dilemma: how to reconcile different social significance of certain religions with the principle of equality of all religions in a secular state. Third, expectation of quick secularization according to quick modernization of societies after 1989 and different social reforms they are undertaking is already shifting the scientific focus from the revitalization to further diminishing of social relevance of religion. Expected secularization will certainly shape future debates about consequential impacts of religion in secularized Europe. Yet, this debate is both possible and needed in the light of the fact that many post-Communist countries are already today more secular (atheist?) in comparison to many Western European countries. It is, however, very interesting that these consequential aspects have been up to now more revealed by theologians than sociologists from Eastern European countries. Starting from the normative approach they have rightly noticed that “ new religiosity” does not in many cases mean the rise of “ true believers” . New and welcomed public position of religion was immediately jeopardized by false believers and new threats coming from an increasingly secularized society. In communism so desperately dreamed liberty could be now even seen as a gift from a devil and the question spontaneously arises: why, at all, do we need liberty?